Pengembangan Media Interaktif Berbasis iSpring Presenter pada Materi Bahasa Arab Madrasah Ibtidaiyah - Risa Gowwiyuningsih (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The use of learning media that has been applied so far still has various shortcomings, both in terms of design, material, and language. Based on these problems, the author formulates the research problem, namely: